På spaning efter det offer som ej flytt: Bemästrande av människohandelsoffer och viljans inverkan på lagföringen - Märta C. Johansson (Nordisk Tidsskrift for Kriminalvidenskab, 2017)
Despite the relatively high number of police complaints filed in Sweden for human trafficking, few offenders are prosecuted and convicted. While a third of human trafficking complaints are made for other forms of exploitation, e.g., forced labour, convictions primarily concern trafficking for sexual exploitation plus a few cases of forced begging. The current article examines the absence of prosecutionsand convictions in light of the discussion about the character of the crime and its regulation in the Swedish Criminal Code as a crime against peace and freedom. The author concludes that the limited number of convictions, and their restriction to only two forms of trafficking, are not primarily due to resource constraints. Instead they are due to the perceptions of trafficking held by the Swedish criminal courts and to the courts’ notions of what it means to ‘master’ a victim and the types of evidence required to prove such ‘mastery’.